A GIS-based model for simulating the hydrological effects of land use changes on karst systems – The integration of the LuKARS model into FREEWAT - Bittner, Daniel; Rychlik, Ayla; Klöffel, Tobias; Leuteritz, Anna; Disse, Markus; Chiogna, Gabriele (ENVIRON MODELL SOFTW, 2020)
Simulating karst spring discharge and land use change impacts in a recharge area is strategic for water resource management in many countries worldwide. We introduce a user-friendly modeling environment by integrating the recently proposed LuKARS (Land use change modeling in KARSt systems) model into the FREEWAT (FREE and Open Source Software Tools for WATer Resource Management) framework. LuKARS is a rainfall-discharge model for karst systems that simulates the impact of land use changes by changing the area of dominant hydrotopes, i.e. landscape units with homogeneous soil and land use properties. FREEWAT is a free and open source toolkit for water resource management implemented in QGIS desktop application. The integration of LuKARS into FREEWAT takes advantage of the GIS capabilities to map, visualize and change the relevant hydrotope shapefiles. FREEWAT provides a modular framework for pre- and post-processing tools that facilitate the setup, calibration, analysis, storage and sharing of LuKARS models.
CRIS-Team Scopus Importer:2024-04-17